Studying the element of strength characterized by speed among football players during the stage of formation and preparation of Latakia clubs (Latakia University Journal -Medical Sciences Series, 2024)
The training and development of the element of strength characterized of speed at the stage of formation and preparation of football players is one of the important factors in the success of the training program for coaches, which requires great attention to this physical element, which has a role and great importance in improving motor skills such as shooting and deception,it also contributes to improving special physical abilities and tactics such as starting, jumping and the power of high balls with the head.The team that bounces individuals high is relatively superior,especially with vertical balls,more than the of strength characterized of speed among football players in Latakia before and after the completion of the training and preparation phase and to identify the level of change in it.After conducting the test and completing it completely, the results were collected,statistically processed, presented and discussed in a scientific manner in order to achieve the research goal and at the end of the research we came to a clear difference in the two research sample